Distinct white-matter aberrations in 22q11.2 deletion syndrome and patients at ultra-high risk for psychosis. Issue 11 (19th May 2016) - Bakker, G.; Caan, M. W. A.; Schluter, R. S.; Bloemen, O. J. N; da Silva- Alves, F.; de Koning, M. B.; Boot, E.; Vingerhoets, W. A. M.; Nieman, D. H.; de Haan, L.; Booij, J.; van Amelsvoort, T. A. M. J.
Abstract : Background: Patients with a deletion at chromosome 22q11.2 (22q11DS) have 30% lifetime risk of developing a psychosis. People fulfilling clinical criteria for ultra-high risk (UHR) for psychosis have 30% risk of developing a psychosis within 2 years. Both high-risk groups show white-matter (WM) abnormalities in microstructure and volume compared to healthy controls (HC), which have been related to psychotic symptoms. Comparisons of WM pathology between these two groups may specify WM markers related to genetic and clinical risk factors. Method: Fractional anisotropy (FA), axial diffusivity (AD), radial diffusivity (RD) and mean diffusivity (MD) were assessed using diffusion tensor magnetic resonance imaging (MRI), and WM volume with structural MRI, in 23 UHR patients, 21 22q11DS patients, and 33 HC. Results: Compared to UHR patients 22q11DS patients had (1) lower AD and RD in corpus callosum (CC), cortical fasciculi, and anterior thalamic radiation (ATR), (2) higher FA in CC and ATR, and (3) lower occipital and superior temporal gyrus WM volume. Compared to HC, 22q11DS patients had (1) lower AD and RD throughout cortical fasciculi and (2) higher FA in ATR, CC and inferior fronto-occipital fasciculus. Compared to HC, UHR patients had (1) higher mean MD, RD, and AD in CC, ATR and cortical fasciculi, (2) no differences in FA. Conclusions: UHR and 22q11DS patients share a susceptibility for developing psychosis yet were characterized by distinct patterns of WM alterations relative to HC. While UHR patients were typified by signs suggestive of aberrant myelination, 22q11DS subjects showed signs suggestive of lower axonal integrity.